Quality Characteristics and Volatile Components of Chili Oil Prepared from the Combination of Shuanla and Erjingtiao Peppers - Fang Yang; Simin Yao; Haibin Yuan; Can Yuan; Hongfeng Jia (Molecules)
This study aimed to investigate the influence of varying weight ratios of Shuanla and Erjingtiao peppers (10:0, 8:2, 6:4, 5:5, 4:6, 2:8, and 0:10, corresponding to samples PA, PB, PC, PD, PE, PF, and PG, respectively) on the sensory attributes, chromatism, acid values (AVs), peroxide values (POVs), capsaicinoids, and volatile organic compounds (VOCs) of seven chili oil samples. GC–IMS was employed to detect the VOCs of the chili oil samples, which were subsequently analyzed using multivariate statistical methods. The results revealed significant differences in pungency among the samples, with the PA sample exhibiting the strongest pungency. The PG sample demonstrated the highest values for a*, b*, and C*, while the PA sample displayed the highest L* and h*. The AVs of seven samples ranged from 0.490 ± 0.005 to 1.727 ± 0.015 mg/g. The POVs of the chili oil samples, ranging from 0.094 ± 0.000 to 0.127 ± 0.002 g/100 g, were significantly lower than those of extra virgin olive oil, 0.183 ± 0.001 g/100 g. The contents of capsaicinoids ranged from 15.26 ± 0.07 g/kg in the PA sample to 0.38 ± 0.00 g/kg in the PG sample (p < 0.05). Additionally, 56 volatile flavor substances were identified, and 10 key flavor compounds (ROAV ≥ 1) were screened among them. Multivariate data analysis via OPLS-DA indicated that 20 VOCs (VIP > 1) could serve as flavor markers in a clustering heat map to differentiate among the seven chili oil varieties. The findings of this study provide a valuable reference for the promotion of Shuanla and Erjingtiao peppers in chili oil production and the development of specific flavor profiles in chili oil to cater to diverse consumer preferences.